Pergeseran Praktik Berbahasa Siswa SD di Ruang Kelas akibat Paparan Konten Viral “Ballerina Cappuccino” - Masyitah Dapidfatma; Meri Safitri; Safrizal; Desty Ayu Anastasha (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
The rapid growth of social media has contributed to noticeable changes in the language acquisition process of elementary school students. This study focuses on the viral content “Ballerina Cappuccino,” which has been widely imitated by students, especially in terms of pronunciation, intonation, and the use of repeated vocabulary. The purpose of this research applies a qualitative approach with a case study design and involves four informants selected through a snowball sampling technique. Data were collected through in-depth interviews and analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The findings show that the viral content affects students’ language acquisition in three main aspects: (1) changes in speech style and prosody based on imitated intonation, (2) dominance of repetitive conversation topics related to the viral content, and (3)the emergence of foreign or meaningless imitative expressions in everyday interactions. These findings indicate that social media, particularly viral content. Has become a competing linguistic input alongside formal learning environments. Therefore, this phenomenon highlights the need for guided digital literacy and monitoring of language use to ensure that students’ language acquisition develops in a balanced and directed manner.